UNIVERSITY COMMITMENT AND SOCIAL RESPONSIBILITY WITH ENTREPRENEURS: A CASE STUDY IN THE PERUVIAN CONTEXT - Robles Fabián, Daniel Amadeo; Silvera Arcos, Susan Madeleine; Pedroza San Miguel, Rosa Diana; Cosme Silva, Omar; Balvin Azaña, Román Junior (LACCEI, 2025)
The purpose of this study was to verify how university social responsibility and commitment influence entrepreneurs in the Puente Piedra district of Lima city using the hypothetical-deductive method, quantitative approach, non-experimental design, explanatory scope and transactional cut. The study unit had as probabilistic sample 394 entrepreneurs, the survey as technique and three questionnaires structured in dimensions and indicators on a Likert scale for all items as instruments. The inferential results of non-parametric tests such as multivariate linear regression affirmed that university social responsibility and commitment positively influence entrepreneurs with a p-value 1.96. In conclusion, it can be stated that universities have the skills to offer comprehensive support to entrepreneurs, enhancing the capabilities of their students, teachers and administrators, contributing to the economic and social development of communities.